Association of BRCAI Epigenetic, with Breast Cancer - methylation, unmethylation, BRACA1, modification, CPG (Institute of Medico-legal Publications Pvt Ltd, 2020)
Breast cancer is the most frequent malignancy among Iraqi women cancer. Epigenetic alterations such asDNA methylation were involved in the earliest phases of tumorigenesis and help for early diagnoses ofbreast cancer.In this study, the methylation and unmethylation BRACA1 gene have been detected of Iraqi women patientshaving breast cancer.DNA extraction kit and DNA modification kits as well as polymerase chain reaction (PCR) have been used.The samples of 80 women patients’ blood with breast cancer and 20 apparently healthy individual’s bloodsample are collected during the period of February2018- April2018 from Oncology Hospital in the MedicalCity - Baghdad, Iraq.On using PCR(24) out of (80)patients havingmethylated BRACA1 and (56) having unmethylated BRACA1.As discussed in this thesis, one can recommend by using BRACA1 gene as biomarker for prediction of earlydiagnoses.